2018
DOI: 10.1371/journal.pone.0204052
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of a motion capture system on Microsoft Kinect v2 recordings: A caution for using the technologies together

Abstract: Microsoft Kinect sensors are considered to be low-cost popular RGB-D sensors and are widely employed in various applications. Consequently, several studies have been conducted to evaluate the reliability and validity of Microsoft Kinect sensors, and noise models have been proposed for the sensors. Several studies utilized motion capture systems as a golden standard to assess the Microsoft Kinect sensors, and none of them reported interference between Kinect sensors and motion capture systems. This study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…As mentioned by Naeemabadi et al [ 28 ], retro-reflective markers, like those of the Vicon system, appear as noise in the IR images, so their 3D position is unknown to the Kinect sensors. To determine the 3D position of the Vicon markers, nevertheless, the intermediate intersection points on the chessboard were identified in the 2D color images using the OpenCV library, followed by the coordinate mapper functions provided by the Kinect SDKs to obtain the actual 3D positions from the depth camera space, denoted as points in the point set P .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…As mentioned by Naeemabadi et al [ 28 ], retro-reflective markers, like those of the Vicon system, appear as noise in the IR images, so their 3D position is unknown to the Kinect sensors. To determine the 3D position of the Vicon markers, nevertheless, the intermediate intersection points on the chessboard were identified in the 2D color images using the OpenCV library, followed by the coordinate mapper functions provided by the Kinect SDKs to obtain the actual 3D positions from the depth camera space, denoted as points in the point set P .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…In our preliminary recordings and a previous study (Naeemabadi et al, 2018), it was observed that infrared markers placed on the ankle and knee for optical motion capture could hinder the recording of depth images by the Azure Kinect sensor. Instead of placing a marker on the knee and ankle, we created a rigid body model for the shank segment before the recording session.…”
Section: Methodsmentioning
confidence: 75%
“…In addition, the synchronization between the sensors constrains the Qualisys system to work at 30 Hz instead of 300 Hz. Naembadi et al studied this question with Kinect 2, but Kinect 3 seems to be much more sensitive to interference [21]. Another point to highlight is the computational cost for running Kinect 3.…”
Section: Discussion and Limitsmentioning
confidence: 99%